Preformulation and formulation of an anti-inflamatory ophathalmic solution from emilia sonchifolia L. DC. leaf and stem extract - Punzal, Jerald Patrick J.; Uno, Karl S.; Vazquez, Trisha Elysse T.
Uveitis includes a group of inflammatory diseases that leads to swelling and destruction of eye tissues. Emilia sonchifolia L. DC., locally known as Tagulinaw, is a common herbal weed found in tropical and subtropical countries which has shown anti-inflammatory activity in different studies. In this study, the anti-inflammatory activity of Tagulinaw against lipopolysaccharide induced eye inflammation was assessed. The study has conducted Artemia salina L. (Brine Shrimp) lethality assay to estimate a non-toxic dose, followed by in-vitro protein denaturation assay to estimate an effective dose within the non-toxic dose determined from the lethality assay. From the lethality assay, it was concluded that the ethyl acetate maceration is non-toxic to brine shrimps at 10-1000ug/mL., and the protein denaturation assay concluded that the aqueous isolate at 500ul/5mL. and the alkaline saponification isolate at 125pg/5mL. has shown the highest inhibitory activity. The final estimated non-toxic and effective fraction/isolate was rendered sterile at physiologic pH and was instilled into Oryctolagus cuniculus (New Zealand white rabbit) eyes (n=16). The aqueous humour was then withdrawn and the resulting PGE2 concentration per treatment were compared. Across all treatment, only the positive and the negative control groups show significant difference while the aqueous fraction and the alkaline saponification isolate show significant difference with neither the control groups. Increasing the amount of plant extractive in the formulation is recommended to observe more pronounced and significant anti-inflammatory activity.